Das Bild der Zwischenstadt. Dekodierung und Inszenierung "Räumlicher Identität" als Potenzial zur Qualifizierung der verstädterten Landschaft". - Bölling, Lars (My University, 2008)
Die Arbeit will einen Beitrag zu einer Qualifizierung der Zwischenstadt leisten. Der Begriff "räumliche Identität" steht dabei im Mittelpunkt: In deren Dekodierung und gegebenenfalls Inszenierung wird ein Potenzial erkannt, die Zwischenstadt als Gestaltungsfeld ins Blickfeld zu rücken und die Aufenthalts- und Erlebnisqualität dieses für die Mehrzahl der Bewohner der Stadtregion prägenden Lebensraums zu verbessern. Die Arbeit unternimmt am Beispiel der Region Rhein-Main eine eigene Annäherung an das Bild der Zwischenstadt. Baustein für Baustein wird versucht, die Sprache, den Code dieses Raumes zu entziffern. Dabei werden Methoden der Beschreibung und Darstellung entwickelt, die der spezifischen räumlichen Eigenschaft der Zwischenstadt gerecht werden. Die Ergebnisse entheben die Zwischenstadt aus ihrer vermeintlichen Eigenschaftslosigkeit. In der Masse raumfunktional organisierter Siedlungsbausteine werden Orte mit Bedeutung, Zusammenhänge und Raumgeschichten lesbar, zeigen sich Verdichtungen und Ansätze einer eigenen Urbanität. Die Arbeit greift die unverkennbare Transformation des Bildes der Zwischenstadt als Chance zur Qualifizierung dieses Raumes auf und entwickelt Modelle, die der Tendenz zu Segregation und Abtrennung mit einer neuen Integrationskultur für die Zwischenstadt begegnen. Hierfür angemessene und auratische Raumbilder zu finden oder zu inszenieren, ist angesichts des Status quo der Stadtlandschaft eine entscheidende Herausforderung.

In The Image of the Zwischenstadt ("Das Bild der Zwischenstadt") possibilities are sought to qualify the urbanized landscape, for which Thomas Sieverts coined the term Zwischenstadt. Particular focus is placed on the examination of spatial identity . In its decryption and presentation a potential to improve the attractiveness of experience and quality of life in the Zwischenstadt is to be found. The area examined between the city of Frankfurt am Main and the prosperous communities surrounding it is particularly suited to decrypt the anatomy of the Zwischenstadt. Layer by layer the attempt is made to decipher the unique language of this space. At the same time, methods of description and presentation are being developed which are capable of doing justice to the specific spatial qualities of the Zwischenstadt. The results of this examination show that the Zwischenstadt has undergone significant changes and release it from its supposed facelessness. Rather, places with meaning, context and history emerge; the beginnings of an independent urbanity and centrality can be seen. The Zwischenstadt has been able to detach itself from its one-sided dependence on the central city, while at the same time undergoing a comprehensive transformation to cope with the changes in needs and ways of life. By no means do the older neighborhoods of single family homes and large residential estates which had characterized the area, or single-function industrial areas and typical suburban shopping centers, continue to automatically fulfill the housing requirements and desires of a leisure society in a service economy. The paper seizes the unmistakable transformation in the image of the Zwischenstadt as an opportunity to qualify this space. Qualification models are developed within it which confront the tendency for segregation and separation with a new culture of integration for the Zwischenstadt. As the formative living environment in the urban area, the Zwischenstadt must satisfy most of the needs its inhabitants and consumers have regarding the area. Increasingly, these needs are not only of a functional variety, but are being superimposed by a need for spatial quality, a sense of belonging and the ability to identify with the area. Given the status quo, finding and producing appropriate and auratic spatial defining elements remains an important challenge.
The Image of the Zwischenstadt. Decoding and creating spatial identity as a way to improve the urbanised landscape.
Keywords: Stadtentwicklungsplanung; Stadtregion; Segregation; Stadtumland; Stadtlandschaft; Verstädterung; Suburbanisierung; Verdichtung; Stadtgestaltung; Urbanität; Bebauung; Fallstudie; Zwischenstadt; Ikonographie; Urbanisierung; Erlebnisqualität; Aufenthaltsqualität